PENGARUH E-WOM, HALAL AWARENESS, INFLUENCER MARKETING DAN LIFESTYLE TERHADAP KEPUTUSAN PEMBELIAN PRODUK MAKANAN IMPOR DALAM KEMASAN - Dewi, Shanaya Rifiana; Gunanto, Edy Yusuf Agung (Jurnal Ekonomi dan Bisnis, 2023)
Purchasing decisions are part of the consumer's behavior in which the consumer will determine which products to consume. There are many factors that can affect purchasing decisions. This study aims to analyze the factors affecting consumer purchasing decisions on imported packaged food products. The data was obtained through a questionnaire distributed online through google form with a sample of 200 respondents who had bought or consumed imported packaged food products in Jakarta. The method used in this study was Structural Equation Modeling (SEM) with Partial Least Square (PLS) techniques using SmartPLS 3.0 analysis tools. Results show that the E-WOM, halal awareness, influencer marketing and lifestyle variables have a positive and significant effect on the purchase decision of imported packaged food products.